Influence of algal organic matter on MS2 bacteriophage inactivation by ultraviolet irradiation at 220 nm and 254 nm. (January 2019) - Wang, Yulin; Araud, Elbashir; Shisler, Joanna L.; Nguyen, Thanh H.; Yuan, Baoling
Abstract: We determined the potential interference of extracellular algal organic matter (EAOM) and intracellular algal organic matter (IAOM) extracted from Microcystis aeruginosa on MS2 bacteriophage inactivation under UV irradiation at two wavelengths (220 and 254 nm). UV irradiation at 220 nm doubled the inactivation rate of MS2 in water containing EAOM than in organic-free phosphate buffered solution. In contrast, EAOM did not change MS2 inactivation by exposure to UV 254 nm. The presence of IAOM did not significantly influence MS2 inactivation by exposure to either UV 254 or UV 220 nm. To achieve 3 log10 inactivation of MS2, UV254 nm required more than double the dose of UV220 nm (45 mJ/cm 2 vs. 20 mJ/cm 2 ). Linear correlations between the reduction in infectivity and the reduction in genome copies detected by reverse transcription quantitative polymerase chain reaction suggested that genomic damage is the main mechanism responsible for MS2 inactivation in water containing algal organic matter (AOM) by exposure to UV irradiation. These findings suggest that the presence of AOM did not negatively influence MS2 inactivation by either 220 or 254 nm irradiation, and that a lower UV dose of 220 nm irradiation can be used to achieve the same level of inactivation in water containing AOM. Highlights: EAOM leads to an increase in MS2 inactivation by 220 nm irradiation. IAOM does not influence MS2 inactivation by 220 or 254 nm irradiation. MS2 inactivation is linearly correlated with its genome damage.